Emerging therapeutic potential of glucagon-like Peptide-1 receptor agonists in knee osteoarthritis: a systematic review - Li, Yapeng; Yang, Lanbo; Li, Feng; Fu, Jia; Zhao, Wangyu; Wu, Xiaolong; Guo, Jiayi; Yue, Chen (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to systematically investigate the clinical efficacy and mechanisms of glucagon-like peptide-1 (GLP-1) receptor agonists (GLP-1 RAs) in the treatment of knee osteoarthritis (KOA), elucidate their underlying mechanisms, and propose potential future research directions.DesignThis study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We reviewed literature from PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov up to 31 December 2024. The search strategy combined “GLP-1″ and “KOA”. We included studies on GLP-1 RAs and KOA in humans and animals, excluding conference abstracts, reviews, letters, case reports, and other similar types of publications.FindingsFifteen studies were included, covering six clinical investigations and nine fundamental research studies. Clinical evidence showed GLP-1 RAs significantly improved pain scores and function while reducing KOA incidence. Mechanistic studies reveal multi-target effects, including: 1) Metabolic regulation, 2) Anti-inflammatory action, and 3) Cartilage preservation through autophagy activation and apoptosis inhibition. Safety analysis notes gastrointestinal and tumor events. At the same time, we are concerned about a declining trend in long-term compliance with GLP-1 RAs.ConclusionThese findings positioned GLP-1 RAs as promising disease-modifying agents for metabolic-associated KOA, particularly in obese or diabetic subpopulations. While current evidence supports therapeutic potential, confirmatory phase III trials and long-term safety monitoring are needed to establish clinical guidelines.Systematic Reviewhttps://www.crd.york.ac.uk/PROSPERO2/view/CRD420250656321, Identifier, CRD420250656321.